Efektivitas Pajak Barang Mewah Ditanggung Pemerintah (PPnBM DTP) terhadap Daya Beli Masyarakat pada Mobil Listrik Berbasis Baterai - Dewi Nur Huly; Rima Herlista; Euis Salma; Rizka Malia; Muhammad Husaini (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
The Covid-19 pandemic significantly affected national economic performance, including the automotive industry which experienced a decline in production and sales. To address this issue while promoting a transition to environmentally friendly energy, the government introduced the Luxury Goods Tax Borne by the Government (PPnBM DTP) incentive for battery electric vehicles under Minister of Finance Regulation No. 9 of 2024. This study aims to evaluate the effectiveness of the policy on public purchasing power. The research applies a descriptive qualitative evaluative method using secondary data from regulations and previous studies. The findings reveal that the PPnBM DTP incentive has increased consumer interest and sales of electric cars in Indonesia, although the growth is not evenly distributed across all market segments. The main barriers remain the relatively high prices of electric vehicles and the limited availability of charging infrastructure. These results imply that additional policy support, particularly in infrastructure development and extended incentives, is essential to strengthen public purchasing power and encourage broader adoption of electric vehicles.